Adaptive controller for the double‐sided linear switched reluctance motor based on the nonlinear inductance modelling. Issue 1 (1st January 2013) - Pan, J.F.; Zou, Yu; Cao, Guangzhong
Abstract : A linear switched reluctance motor (LSRM) is an attractive candidate for high‐precision position control applications in industry. Compared to its single‐sided counterpart, a double‐sided LSRM (DLSRM) has a more propulsion force to mass ratio and normal force can be counteracted from serially connected excitation windings and a symmetric machine structure. In this study, a nonlinear inductance modelling method is proposed by introducing a K factor that reflects both current and position effect on inductance. Considering uncertainties and disturbances from the DLSRM‐based motion system, this study implements online parameter estimation with adaptive control strategy to detect system parameter variations and regulate control parameters in real time. Experimental results demonstrate that the proposed control method is capable of position tracking with the desired performance and adaptive to operational changes either under command signal variations or external disturbances. These results prove the effectiveness of the proposed control method for high‐precision position control of the DLSRM.